The The Influence of Company Growth, Return on Investment, and Earnings per Share on Stock Prices of PT. Kimia Farma and PT. Indofarma Before and During the Covid-19 Pandemic - Hati, Ravika Permata; Ridianto, Rini; Siregar, Hanafi; Destami, Gina Dery; Halim, Yulita Zulkarnaen; Pasribu, Rohana Marito; Suryani, Arna (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The aim of this research is to determine the influence of company growth, return on investment and earnings per share on share prices at PT. Kimia Farma and PT. Indofarma both in the period before and during the Covid-19 pandemic as well as differences in Company Growth, Return on Investment and Earnings per Share of PT. Kimia Farma and PT. Indofarma between before and during the Covid-19 pandemic. This type of research is quantitative using panel data regression analysis and difference tests as data analysis methods. The data used are financial reports taken from the Indonesian Stock Exchange. The research results show that: partially, company growth in the period before the Covid-19 pandemic did not have a significant effect on share prices, Company growth during the Covid-19 pandemic had a significant effect on share prices, Return on Investment in the period before and during the Covid-19 pandemic. has a significant effect on share prices, Earnings per Share in the period before and during the Covid-19 pandemic did not have a significant effect on share prices. Meanwhile, the results of different tests on Company Growth, Return on Investment and Earnings per Share did not have significant differences between before and during the Covid-19 pandemic.